[ (5 to the power -1 * 3 to the power -1) to the power -1 / 6 to the power -1] to the power 2

Asked by samruddhikhedkar85.8spicertl | 6th Jun, 2020, 12:20: PM

Expert Answer:

To find the value of the expression [(5-1 * 3-1)-1/6-1]2
This can be solved using the laws of exponents
As we know that 1/a = a-1, am * an = am+n and (am)n = amn, we have
[(5-1 * 3-1)-1/6-1]2
= [(5-1 * 3-1)-1 * 61]2
= [(5-1)-1 * (3-1)-1 * 61]2    .... Since (ab)m = am bm
= [5-1x(-1) * 3-1x(-1) * 6]2
= [5 x 3 x 6]2
= (90)2
= 8100
Hence, [(5-1 * 3-1)-1/6-1]2 = 8100

Answered by Renu Varma | 6th Jun, 2020, 02:13: PM